Revisit the Effectiveness of Educational Kinesiology on Stress and Anxiety Amelioration in Kindergarteners With Special Needs Using Biological Measures - Tai, Alan Pui-Lun; Lau, Way Kwok-Wai (Frontiers in Psychiatry, 2021)
Background: Educational kinesiology is a popular intervention that aims to improve brain functioning via physical movements. Yet, it lacks supporting scientific evidence and is regarded as pseudoscience. Given the popularity of educational kinesiology in school settings, it is important to revisit its effectiveness through scientific research. Previous studies that evaluated the effectiveness of educational kinesiology relied mainly on subjective measures, in which subjective bias is inevitable. Cortisol and oxytocin levels in saliva have been reported to be reliable stress and anxiety markers that provide unbiased objective data. This study explores the effect of educational kinesiology on the changes in salivary cortisol and oxytocin levels in kindergarteners with special needs. Methods: A quasi-experimental design was adopted in this study. Thirty-seven kindergarteners (3.5–6.5 years old) who were either diagnosed with one type of special needs or referred by school principals due to the requirement of special supports at school were assigned to either the intervention group, which received 1-h educational kinesiology intervention weekly for a total of 10 weeks, or the wait-list control group. Saliva samples were collected at baseline and after the completion of intervention programme for the measurement of cortisol and oxytocin levels. Scores of Parent-rated Preschool Anxiety Scale (PAS-TC) were also collected at pre- and post-intervention. Because of the small samples, non-parametric tests such as Mann-Whitney U test, Quade test, and Fisher's exact tests were used in this study where appropriate. Results: After controlled for the effect at baseline, gender and types of special needs, the changes in oxytocin levels were significantly higher in the intervention group compared with control [F(1, 35) = 4.747, p = 0.036, eta2 = 0.119], whereas no significant between-group difference in changes of cortisol levels was observed [F(1, 35) = 0.306, p = 0.584, eta2 = 0.009]. Results from PAS-TC showed significant improvement in anxiety levels after the intervention in the intervention group (p = 0.048, ϕ = 0.344, p = 0.037). Conclusions: Our findings suggest a plausible anti-anxiety effect of educational kinesiology in kindergarteners with special needs by elevating the oxytocin levels. Future studies are warranted to further confirm our findings with a larger sample.